Permanent pacemaker insertion in a district general hospital: indications, patient characteristics, and complications. Issue 896 (1st June 2000) - Eltrafi, A; Currie, P; Silas, J H
Abstract : This report reviews the experience of permanent pacemaker insertion in a district general hospital (catchment population of 350 000) and makes a comparison with the national database and other hospitals in the UK. METHODS: The records of all patients receiving a permanent pacemaker in the inclusive period January 1996 to December 1998 were reviewed. Data collected included number of patients paced each year, age, sex, indications, and complications. RESULTS: In the three years reviewed 200 patients received new permanent pacemakers, a rate of 190 per million population per year, which is similar to the national implantation rate of permanent pacemakers but lower than that of most European countries (see discussion). The majority of patients paced were elderly (75% were above the age of 70 years). Atrioventricular block (including complete heart block, 45%, and Mobitz type 2 block, 12.5%) was the commonest indication for permanent pacemaker insertion, followed by sick sinus syndrome (25%) and these findings are comparable to those reported previously. However, carotid sinus syndrome was responsible for 16% of the patients paced and this was higher than that reported in the national database (6.5%). Only 1% of the pacemaker modes used was inappropriate and the complication rate was low at 3%. CONCLUSIONS: This report confirms that permanent pacemaker insertion can be effectively and safely provided locally for the increasingly ageing population. The implantation rate both locally and nationally is still much lower than that of some countries in Europe.